PENGEMBANGAN PENDIDIKAN KARAKTER MELALUI METODE PEMBIASAAN DAN KETELADANAN - Luqman, Asasuddin (STAIN Ponorogo, 2014)
Abstract: The character is a subject of an education that is very interesting and always discussed by educators in educational practice today. The Quran as an educational book also teaches the importance of both; morality education (aqidah) and character education (akhlaq), which are an integral and inseparable. This shows the importance of education and character building in every educational process at all levels. Despite the struggle between good characters and bad characters in every human being, but basically a good character can be formed through the soul treatment, habituation of right conduct, exemplary and good social environment. The teachers are demanded to treat a pupilâs soul and habituation right conduct so that the pupils have a good character. Besides a good social environment, the more important in order to build the character is the teacher should be an exemplary model for the surrounding community. Rosululloh is the best role model for anyone who wants to follow his character in order to be a person who has a noble character.Â Ù ÙØ®Øµ: Ø¥Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© Ù ÙØ¶ÙØ¹ ØªØ±Ø¨ÙÙ Ø¬Ø°ÙØ§Ø¨ ÙÙØ§ÙØ´ÙØ§ Ø§ÙÙ Ø±Ø¨ÙÙ Ø§ÙØ¢Ù ØªØ·Ø¨ÙÙÙØ§. ÙØ§ÙÙØ±Ø§Ù ÙÙØªØ§Ø¨ ØªØ±Ø¨ÙÙ ÙØ¹ÙÙÙ ÙØ§ Ø´ÙØ¦ÙÙØ ÙÙ Ø§ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¹ÙØ¯ÙØ© ÙØ§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© ÙÙÙ Ø§ Ø´ÙØ¦ ÙØ§ØØ¯ ÙØ§ ÙØªØ¬Ø²Ø£. Ø¯Ù ÙØ°Ø§ Ø¹ÙÙ Ø£ÙÙ ÙØ© Ø§ÙØªØ±Ø¨ÙØ© ÙØ¨ÙØ§Ø¡ Ø§ÙØ£Ø®ÙØ§Ù ÙÙ Ø¬Ù ÙØ¹ Ù Ø³ØªÙÙØ§Øª Ø§ÙØ¹Ù ÙÙØ© Ø§ÙØªØ±Ø¨ÙÙØ©. ÙÙ ÙÙ Ø§ ÙÙØ§Ù ØµØ±Ø§Ø¹ Ø¨ÙÙ Ø§ÙØ£Ø®ÙØ§Ù Ø§ÙÙØ±ÙÙ Ø© ÙØ§ÙØ£Ø®ÙØ§Ù Ø§ÙØ°Ù ÙÙ Ø© ÙÙ Ø§ÙØÙØ§Ø©Ø ÙØ¥Ù Ø§ÙØ£Ø®ÙØ§Ù Ø§ÙÙØ±ÙÙ Ø© ÙÙ ÙÙ ØªÙÙÙÙÙØ§ Ø¹Ù Ø·Ø±ÙÙ Ø§ÙØªØ¹Ø§Ù Ù Ø§ÙÙÙØ³ÙØ ÙØªØ¹ÙÙØ¯ Ø£ÙØ¶Ù Ø§ÙØ£Ø¹Ù Ø§ÙØ ÙØ¨Ø§ÙÙ Ø«Ø§Ù ÙØ§ÙØ¨ÙØ¦Ø© Ø§ÙØ§Ø¬ØªÙ Ø§Ø¹ÙØ© Ø§ÙØ¬ÙØ¯Ø©. ÙÙØ±Ø¬Ù Ø£Ù ÙØ¹Ø§Ù Ù Ø§ÙÙ Ø¯Ø±Ø³ Ø·ÙØ§Ø¨Ù ÙÙØ³ÙØ§ ÙØ£Ù ÙØ¹ÙÙØ¯ÙÙ ÙØ¹Ù Ø§ÙØ®ÙØ±Ø§Øª ÙÙÙÙÙ ÙÙÙ Ø£Ø®ÙØ§Ù ÙØ±ÙÙ Ø©. Ø¨Ø¬Ø§ÙØ¨ Ø§ÙØ¨ÙØ¦Ø© Ø§ÙØØ³ÙØ©Ø ÙØ§ÙØ£ÙÙ Ù Ù Ø°ÙÙ Ø£Ù ÙÙÙÙ Ø§ÙÙ Ø¯Ø±Ø³ ÙØ¯ÙØ© ÙÙ ÙØ°Ø§ Ø§ÙØªÙÙÙÙ ÙÙ Ù Ø¬ØªÙ Ø¹Ù. ÙØ§ÙØ±Ø³ÙÙ Ù ØÙ Ø¯ ØµÙÙ Ø§ÙÙÙ Ø¹ÙÙÙ ÙØ³ÙÙ Ø®ÙØ± Ù Ø«Ø§Ù ÙØ¬Ù ÙØ¹ Ø§ÙÙØ§Ø³ ÙÙ Ø§ÙØ§ÙØªØ²Ø§Ù Ø¨Ø§ÙØ£Ø®ÙØ§Ù Ø§ÙÙØ±ÙÙ Ø©.Â Keywords: Pendidikan karakter, kebiasaan, keteladanan